Virtuosismo en la contemporaneidad: de la invisibilidad al activismo decolonial - Susana Castro Gil (2019)
Introduction: The virtuosity, widely related to the spectacular performative practices of the 19th century, may be reconsidered from the etymological perspective virtus which refers to the good performer and therefore the ideal performer in certain context. The imaginary of a good performer in the actual academic context is permeated by the values of Werktreue framed in the modern episteme, consolidated since the second half of the 19th century. However, more than 150 years later, postmodernity and decolonial debates identify the power of coloniality in modern structures and in this perspective, a reflection was proposed in relation to the contemporary good performer -virtuoso-, delimiting it as an agent that actively works to dismantle the persistent coloniality in its musical universe of human and non-human relationships. Objective: Reflect on the delineations that could configure a good performer -virtuoso- compatible with contemporary questions, considering for this the decoloniality as a non-hegemonic alternative to the modern paradigm. Methodology: a bibliographic survey about modernity/coloniality, decolonialism and instrumental virtuosity in music was developed and a reflection about the decolonial activism in the recognition of multiplicity in interactions with heterogeneous agents -such as performance tradition idiomatism, instrumental technique and composer's sustrata- was developed from the performance proposal process of four works of Latin American repertoire of XX and XXI century: Bambuco Sotareño (c.1930) and Prelude (1936) by Antonio María Valencia; Três Profecias em forma de estudo (1988) by José Antonio Rezende de Almeida Prado; Tiento VI (2000) by Germán Cáceres. Conclusions: considering the virtuoso as the good performer, it is possible to visualize it as a mobile figure delineated by its socio/historical context and the prevailing scale of aesthetic values. Modernity as a Western hegemonic episteme since the second half of the nineteenth century and mainly since the beginning of the twentieth century, has conditioned the characteristics of a good performer, framing it in the ideals of Werktreue, which survives nowadays in certain academic and social contexts. The contemporary good performer corresponds to anotherperformance logic and recognizes the colonial power on the relations interlaced into the modern episteme questioning the foundations of the Werktreue -authenticity, fidelity to the text, absolute truth in musical work and performers invisibilization-, as an active agent, a decolonizer activist. The decolonia activism portrayed in this work is clearly noticeable in the action of mediation and recognition of the alterity and the creative agency that comes not just from the composer or the text, but from an extensive network of human and non-human interlocutors that are constituent part of the musical process, assuming the constituen potentially infinite multiplicity of the musical work.